2005
DOI: 10.1007/s11159-005-1842-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantity Versus Quality in Education: Case Studies in Malawi

Abstract: Free primary education was introduced to Malawi in 1994, and it led to an increase in enrolment of one million pupils. The present contribution gathers case studies of 10 schools which sought information on the general conditions of communities and schools as well as on enrolment, resources, staffing, absenteeism etc. The results highlight the difficulties of implementing Education for All (EFA). Generally speaking, schools have been poorly supplied by the state. Effectively, many pupils have been marshaled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 1 publication
2
35
0
Order By: Relevance
“…Luykx (1999) found that Bolivia, a developed country, also faced serious shortages of instructional materials similar to the findings of this study that there are serious shortages of instructional materials in Malawi. Again, as in this study, Chimombo's (2005), Nsapato's (2005), Lowe's (2008) and Kadzamira's (2006) also found that Malawi has the lowest percentage of the availability of textbooks for both teachers and pupils in the sub-Saharan region and that the primary school system in Malawi lacks teaching and learning materials, especially in the rural primary schools, which affect the successful implementation of the primary school curriculum.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Luykx (1999) found that Bolivia, a developed country, also faced serious shortages of instructional materials similar to the findings of this study that there are serious shortages of instructional materials in Malawi. Again, as in this study, Chimombo's (2005), Nsapato's (2005), Lowe's (2008) and Kadzamira's (2006) also found that Malawi has the lowest percentage of the availability of textbooks for both teachers and pupils in the sub-Saharan region and that the primary school system in Malawi lacks teaching and learning materials, especially in the rural primary schools, which affect the successful implementation of the primary school curriculum.…”
Section: Discussionsupporting
confidence: 70%
“…It is not clear how this will be resolved. Studies by Chimombo (2005) and Nsapato (2005) show that primary schools in Malawi face serious shortage of instructional materials that affect the effective implementation of the school curricula. These authors argue that Malawi has the lowest percentage of the availability of textbooks for both teachers and pupils in the sub-Saharan region.…”
Section: Materials Developmentmentioning
confidence: 99%
“…In contrast, the probability of a student's dropping out is higher when the student comes from a larger household or a Muslim household. Other factors that affect the drop-out rate are household poverty, delays in enrolment, the cost of schooling, a lack of interest in education, and early marriage (e.g., Kadzamira and Rose, 2003;Chimombo, 2005;Manda and Meyer, 2005;Moyi, 2010). The poor quality of education is another weakness of Malawi's education system.…”
Section: Educationmentioning
confidence: 99%
“…The poor quality of education is another weakness of Malawi's education system. Chimombo (2005) highlighted a series of factors that can compromise the quality of education, including the scarcity of equipment required for effective teaching (e.g., textbooks, desks), poor condition of many schools, and low teacher-student ratio (this ratio ranged from 1:142 in the Salima school district to 1:53 in the Lilongwe school district). It is important to note that the goal of universal primary education cannot be attained without ensuring school quality because increasing the number of people who complete primary education does not ensure they have the relevant knowledge and skills to make important contributions to the development of the country (Chimombo, 2005).…”
Section: Educationmentioning
confidence: 99%
“…The introduction of free primary education in1994 in Malawi was on the basis that poor people are being left out of school, and that with free access to primary education, it would open a way for them to acquire some education and probably offer a way of escape out of poverty (Chimombo, 2005). There are also other studied like (Psacharopoulos G. , 1994) that found that there are returns that are associated with basic education.…”
Section: Introductionmentioning
confidence: 99%